CD40 ligante solúvel e outros biomarcadores de evolução clínica no tratamento adjuvante da leishmaniose visceral humana com N-Acetilcisteína - Melo, Enaldo Vieira de (2014)
Visceral leishmaniasis constitutes a serious public health problem in the world, demanding effective measures for its control and treatment. The current treatments are far from ideal for the need for prolonged treatment, development of drug resistance and significant side effects. Thus the search for new therapeutic options in addition to evaluating the effectiveness of adjuvant therapy is very important. The aim of this study was to evaluate biomarkers sCD40L and clinical outcome in the adjuvant treatment of human visceral leishmaniasis with N-acetylcysteine. From an intervention study, kind clinical trial, blinded, randomized, were investigated 60 patients from the University Hospital with a positive diagnosis for acute visceral leishmaniasis. These patients were divided into two groups of 30: Study Group - which made use of antimony penta valent standard dose supplemented with N-acetyl-L-cysteine and the control group - which only used the standard dose antimony. The serum levels of soluble ligand sCD40L were significantly higher elevation and steeper over time in SbV + NAC group compared to the Sb group. Furthermore, the distribution of values sCD40L significantly increased in both groups after 15 days of treatment, thereafter no significant change over time. Likewise the size of the spleen, and serum cytokine levels (TNF-α, IL-10, IL-12p40) decreased during treatment in both groups while the number of neutrophils, eosinophils and platelets increased. Several published studies indicate the importance of CD40 / sCD40L interaction for an effective immune response and that this interaction occurs via reciprocal signaling through protein kinase-induced phosphorylation of MAPK p38 and ERK1 / 2 mitogen. Other studies show as a strategy of evading the immune response and the establishment of infection, Leishmania inhibits p38 MAPK signaling triggered by CD40. And the glutathione redox system regulates the production of IL-12 induced by LPS through the activation of p38 MPAK, and furthermore, the effect initiation of IFN-γ and IL-12 is in part a consequence of the equilibrium glutathione redox. NAC was able to increase serum sCD40L concentrations throughout treatment. Treatment with NAC improved the patients´ clinical parameters associated with the prognosis of the patients: reduced spleen size increased number of neutrophils / lymphocytes and eosinophils faster. The results suggest that the addition of NAC to conventional therapy improves the immune response of patients, particularly in the reduction of serum IL-10, IL-12p40 and increase in sDC40L that this response occurs as early as two weeks. It is likely that increased levels of sCD40L the NAC occurs through the activation of p38 MAPK pathway glutathione redox system.